2020
DOI: 10.1002/smll.202004831
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Tumor Targeting by Higher‐Order Glycan Pattern Recognition: Synthesis and In Vitro and In Vivo Properties of Glycoalbumins Conjugated with Four Different N‐Glycan Molecules

Abstract: Natural glycoconjugates that form glycocalyx play important roles in various biological processes based on cell surface recognition through pattern recognition mechanisms. This work represents a new synthesisbased screening strategy to efficiently target the cancer cells by higherorder glycan pattern recognition in both cells and intact animals (mice). The use of the very fast, selective, and effective RIKEN click reaction (6π-azaelectrocyclization of unsaturated imines) allows to synthesize and screen various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Given this promising result, to multiply technique to more selectively target tumors, we developed another approach using higher-order heterogeneous glycoalbumins that were conjugated with four kinds of complex N-glycans. 33 As depicted in Figure 3D-(III), the in vivo data revealed that the higher-order glycoalbumin 3b displayed the strongest targeting towards SW620 tumors than lower-order glycoalbumin 3a�…”
Section: Glycan Targetingmentioning
confidence: 84%
See 1 more Smart Citation
“…Given this promising result, to multiply technique to more selectively target tumors, we developed another approach using higher-order heterogeneous glycoalbumins that were conjugated with four kinds of complex N-glycans. 33 As depicted in Figure 3D-(III), the in vivo data revealed that the higher-order glycoalbumin 3b displayed the strongest targeting towards SW620 tumors than lower-order glycoalbumin 3a�…”
Section: Glycan Targetingmentioning
confidence: 84%
“…As a result, azaelectrocyclization for lysine-selective conjugation (later coined as the RIKEN click reaction 9 -11 ) has become a standard technique heavily utilized in our research today. As shown in Figure 2B, we first began to prepare the aldehyde probe directly linked with molecules of interest via amide linkage� [12][13][14][15][16][17][18] To simplify the operation of the RIKEN click reaction, we transitioned to using another reaction to link the molecules� This has led to the preparation of RIKEN click reagents modified with groups such as a azide (for Staudinger ligation) 19 , dibenzocyclooctyne (for strain-promoted azidealkyne cycloaddition) 20,21 , and trans-cyclooctene (for tetrazine ligation) [22][23][24][25][26][27][28][29][30][31][32][33][34][35] � Numerous successfully applied molecules for protein modification clearly prove the versatility of the RIKEN click reaction. For instance, molecular imaging and radiotherapeutic applications have seen the usage of metal chelating agents, such as DOTA 12,13,18,20,30 , NOTA 20,30 , and closo-decaborate 21 .…”
Section: Therapeutic In Vivo Synthetic Chemistrymentioning
confidence: 99%
“…For targeted prodrug activation, a suitable mechanism was needed to direct the biocatalyst to specific cells or tissues within the body. Previously developed by our group, N-glycosylated albumins have been found to be excellent tools for cancer cell targeting [77][78][79][80][81][82][83] . Observations showed that HeLa cancer cell targeting could be rapidly achieved using an N-glycosylated albumin decorated with a homogenous assembly of α(2,6)-sialic acid terminated complex glycans.…”
Section: Pharmacophore Backbone Screening and Optimizationmentioning
confidence: 99%
“…As a further step, the RIKEN click strategy was applied to the synthesis of heterogeneous glycoconjugates [43,44,47,48]. Tanaka et al developed two approaches, which are based either on the sequential introduction of the first, followed by the second, glycan into the protein molecule (Figure 5b, so-called arbitrarily arranged or positionally un- Although the studied homogeneous glycoclusters 4a-f showed recognition of various cells, including cancer cells, selectivity was not high [43,45].…”
Section: Arbitrarily Arranged Heterogeneous Glycoalbuminsmentioning
confidence: 99%